THE STUDY OF TREE LEVEL IN ANGGOMATE WATERSHED AREA , SOUTHEAST SULAWESI - Ikbal Ikbal; Aqmal Khaery; Fachruddin Fachruddin (Universitas Medan Area, 2021)
Anggomate River has ecological and economic value for the local community. Massive community activities in utilizing land in the Anggomate watershed area for plantation, inhabitation, and sand mining lands can cause the tree vegetation decline, even flood often occurs in Andowia region annually. The research method used was a quantitative method. Sampling was performed through a plot-transect method. The plots were placed on the downstream (Labungga Village river area), middle (Laronaga Village river area), and upstream (Andowia Village river area) regions. The study results showed that there are 35 tree species with the individual number of 64. The highest importance value index was obtained from Ficus benjamina L. at 29.38%, Anthocephalus cadamba (Roxb.) Miq) at 25.64%, and Lansium domesticum Corr. at 16.81%. The dominance index of the tree species in the Anggomate river area was 0.971, which indicates that one of the tree species dominated this area, namely, Anthocephalus cadamba (Roxb.) Miq) (Roxb.) Miq). The diversity index in the Anggomate watershed area includes in high category (H’= 3.402 atau H’ > 3). The distribution index includes in the evenly distribution category due to obtaining closely approaching the value of 1 (E= 0.818).